Situation Report: Hungary, 24 April 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Joint Maneuver of Warsaw Pact States on Hungarian Territory The Anniversary of Lenin's 92nd Birthday Celebrated in Budapest "Dogmatists" of County Nograd Reprimanded Share in Profit in Industry only 1.3 Billion Forints Hungary Grants "De Jure" Recognition to Algerian Provisional Government Soviet Ambassador Informs Kadar on Soviet-US talks on Berlin